Penyerapan Kadmium pada Ayam Kampung yang Diberi Dedak Padi dalam Ransum - D Saefulhadjar; I Hernaman; K A Kamil (Faculty of Animal Science, Bogor Agricultural University, 2008)
Phytate is commonly found in high concentration in rice bran. This compound can bind multivalency ions. The purpose of this study was to know the effect of rice bran in native chicken diet on Cd absorption. Twenty four native male chicks aged 3 months were randomly divided into six groups of treatments. The average weight of chick used in this experiment was 422.08 Ã‚Â± 39 g. The dietary treatments were 0% (R0), 10% (R1), 20% (R2), 30% (R3), 40% (R4), and 50% (R5) of rice bran in the ration given for 8 weeks. Drinking water containing 100 ppm Cd was given ad libitum. The results indicated that those treatments had no significant effect on Cd absorption, Cd concentration in feces, kidney, liver and weight of kidney and liver. Average of Cd in kidney and liver were 284.24 and 117.53 ppm respectively. It was concluded that rice bran in the native chick diet did not reduce Cd absorption. The utilization of rice bran and Cd pollution for long term period and in high concentration in the diet gave negative effect on native chicken performance. Key words: rice bran, phytate, cadmium, native chicken